Electric machinery - Liu, Huijuan; Fan, Yu (New Delhi: Narosa Publishing House, 2018)
ELECTRIC MACHINERY mainly describes the working principles and the steady-state operating characteristics of four kinds of typical general machines, such as DC Machine, Transformer, Induction Machine and Synchronous Machine.
Keywords: Electric machinery -- Electric motors -- Electric generators -- Electromechanical devices -- Power electronics